Bisnis Internasional dan Perusahaan Multinasional - Ria Satyarini (Bina Ekonomi, 2001)
Business World has become "Borderless World" and cannot grow by developing its domestic market only, but also have to take a challenge to make an overseas expansion. There are some differences between domestic and international business. Indeed, international business has more aspects than domestic business, therefore a company has to be more effective when it attempts to make an overseas expansion. This paper will explain about how a company attain a high effectiveness and get ready to enter international business. Several strategies of international Business, such as: exportation, licensing agreement, management contracts, joint ventures and subsidiaries will be elaborated. Finally, Global service strategies, which are: multi country expansion, importing customers, follow your customers, service unbundling, and beating the clock will also be discussed.